Numerical and experimental analysis of combustion in microchannels with controlled temperature. (November 2019) - Bucci, M.A.; Di Stazio, A.; Chauveau, C.; Dayma, G.; Legros, G.; Dagaut, P.; Chibbaro, S.
Highlights: Micro-combustion instabilities are studied through models and experiments. The model reproduces the phase-diagram of the flame dynamics without tuning. We investigate the FREI instability frequency and qualitative agreement is found. Some discrepancy in frequency value shows local properties of the flow are key. Abstract: This paper reports on joint experimental-numerical investigations of flame dynamics in a microchannel of diameter 1.85 mm. Experiments show that decreasing the diameter of the channel helps the arising of the FREI instability. Yet leaning the mixture is found to be a mean to make the flame more stable. The numerical model used is based on two- dimensional thermo-diffusive equations with one-step chemistry, and it is tested against the experimental results without any calibration. The model turns out to reproduce in a satisfactory manner all the features from a qualitative point of view, and most of them from a quantitative point of view, showing robustness not only with respect to geometry but also to equivalence ratio changes. Nonetheless, while the analysis of frequencies of the FREI instability shows a qualitative agreement, a quantitative discrepancy is unfold. The results suggest that instabilities in microcombustion of CH4/air are fundamentally triggered by hydrodynamics.